Karakteristik Campuran Aspal Panas Menggunakan Bahan Campuran RAP (Reclaimed Asphalt Pavement) Pada Berbagai Ukuran Agregat Nominal - Mega, Ulfa Citra; Putra, Sasana; Karami, Muhammad (Universitas Lampung, 2020)
RAP (Reclaimed Asphalt Pavement) is the residual pavement that has been damaged or out of date. RAP can be reused as a basic material for flexible pavement with the addition of new aggregate material and asphalt, to fulfill the quality and specifications of flexible pavement. This study aime to determine the quality of hot mix asphalt at various nominal aggregate sizes that made from RAP (Reclaimed Asphalt Pavement). The results of the study obtained the maximum stability value on the use of RAP 20% in AC-WC obtained 1588,829 kg, while for the use of RAP 22% on AC-BC obtained 1799,405 kg and for RAP on AC-Base 28% has a maximum stability value amounting to 2285,571kg. The three types of mixtures have mixed characteristics and marshall characteristics that fulfill the General Specifications of Bina Marga. The Optimum Asphalt Content value for the percentage of RAP use of 20% in AC-WC was 5.8%. Whereas for the use of 22% RAP on AC-BC, the Optimum Asphalt Content value was 5.45% and the use of RAP on AC-Base 28% was obtained by the Optimum Asphalt Containt value of 4.9%. The greater the nominal aggregate size of the hot asphalt type, the greater the percentage of RAP (Reclaimed Asphalt Pavement) required . Keyword : RAP (Reclaimed Asphalt Pavement), Hot Mix Asphalt, Optimum Asphalt Containt